Perancangan dan Pembuatan Sistem Informasi Akuntansi dan Inventory Control pada Salon Mobil XYZ - Alex Ivan Harjono; Yulia Yulia; Christian Christian (Jurnal Infra, 2016)
At this time, the Car Salon XYZ still record sales, purchase transactions, stock movement, and financial report manually. The Car Salon XYZ still not using structured information systems. Owner often have difficulties of monitoring the amount of stock for each items. Recording process that still done manually often causes some errors that may disturb the business processes in car salon and waste a lot of time. Based on background of that problem on this Car Salon XYZ, we designed a system that can process the operational data transactions, making of stock card and inventory control, and making the complete financial reports. Application made by web-based program using Framework CodeIgniter, PHP as programming tool and MySQl as database of the program. Record of accounting using perpetual method and card stock using FIFO (First In First Out).Results that obtained from the application that have been made, are able to record the transaction of sales and purchases, inventory control that can set a reminder of the stock availability, accounting journal and report of financial statements that required.